Hemolysis inhibits humoral B-cell responses and modulates alloimmunization risk in patients with sickle cell disease - Pal, Mouli (Blood, 2021)
Red blood cell alloimmunization remains a barrier for safe and effective transfusions in sickle cell disease (SCD), but the associated risk factors remain largely unknown. Intravascular hemolysis, a hallmark of SCD, results in the release of heme with potent immunomodulatory activity, although its effect on SCD humoral response, specifically alloimmunization, remains unclear. Here, we found that cell-free heme suppresses human B-cell plasmablast and plasma cell differentiation by inhibiting the DOCK8/STAT3 signaling pathway, which is critical for B-cell activation, as well as by upregulating heme oxygenase 1 (HO-1) through its enzymatic byproducts, carbon monoxide and biliverdin. Whereas nonalloimmunized SCD B cells were inhibited by exogenous heme, B cells from the alloimmunized group were nonresponsive to heme inhibition and readily differentiated into plasma cells. Consistent with a differential B-cell response to hemolysis, we found elevated B-cell basal levels of DOCK8 and higher HO-1–mediated inhibition of activated B cells in nonalloimmunized compared with alloimmunized SCD patients. To overcome the alloimmunized B-cell heme insensitivity, we screened several heme-binding molecules and identified quinine as a potent inhibitor of B-cell activity, reversing the resistance to heme suppression in alloimmunized patients. B-cell inhibition by quinine occurred only in the presence of heme and through HO-1 induction. Altogether, these data suggest that hemolysis can dampen the humoral B-cell response and that B-cell heme responsiveness maybe a determinant of alloimmunization risk in SCD. By restoring B-cell heme sensitivity, quinine may have therapeutic potential to prevent and inhibit alloimmunization in SCD patients.